Gene-Environment Interactions and the Neurobiology of Social Conflict - SUOMI, STEPHEN J. (Annals of the New York Academy of Sciences, 2003)
: Recent research has disclosed marked individual differences in biobehavioral responses to social conflicts exhibited by rhesus monkeys across the life span. For example, approximately 5–10% of rhesus monkeys growing up in the wild consistently exhibit impulsive and/or inappropriately aggressive responses to mildly stressful situations throughout development; those same individuals also show chronic deficits in their central serotonin metabolism. These characteristic patterns of biobehavioral response emerge early in life and remain remarkably stable from infancy to adulthood. Laboratory studies have demonstrated that although these characteristics are highly heritable, they are also subject to major modification by specific early experiences, particularly those involving early social attachment relationships. Moreover, genetic and early experience factors can interact, often in dramatic fashion. For example, a specific polymorphism in the serotonin transporter gene is associated with deficits in early neurobehavioral functioning and serotonin metabolism, extreme aggression, and excessive alcohol consumption among monkeys who experienced insecure early attachment relationships, but not in monkeys who developed secure attachment relationships with their mothers during infancy. Because daughters tend to develop the same type of attachment relationships with their own offspring that they experienced with their mothers early in life, such early experiences provide a possible nongenetic mechanism for transmitting these patterns to subsequent generations.